Librarians’ Group Report on National Information Systems (1984) - World, Information (Information World, 2011)
This report has been prepared librarians sent by private and goverment agencies owing to the call of TUBITAK/TURDOK for a meting on the subject. A sceond report, which was a corrected edition of this report, was presented later.
Keywords: National information systems; TURDOK; Information systems; Librarianship; Libraries; Turkey